Co-Machines : Mobile Disruptive Architecture. - Dorocic, Dan; Hugill, Alison; Plough, Josh ([S.l.] : Onomatopee, 2020)
ON/OFF ; Dorocic, Dan ; Dovey, Kim ; Green, Nick ; Zeiger, Mimi ; Shipwright, Fiona ; Maginness, Michael ; Hugill, Alison ; Barbé, Diane Días Carvalho, Samuel ; Foerster-Baldenius, Benjamin ; Crisan, Ane ; Rachelson, Halina ; Plough, Josh ; Jín, Melissa ; Khouja, Ahmad S. ; Kaegh ; The Office of Urban Play ; Stevermer, Tyler ; RealLabor ; Gantert, Marius ; Office for Political Innovation ; PINKCLOUD.DK ; von Hase, Philipp ; Rosa, Marcos L. ; ContructLab ; SoidOperations ; Cornago, Íñigo & Sánchez, Claudia ; Peachey, Rachel & Mosig, Paul ; Precious Plastic ; Guerilla Architects ; Vigneri-Beane, Jason ; Blomberg, Karin ; Kerner Tal Mor Sinay, Joel ; Orving, Andrea ; Atelier Slant ; v. Lenthe, Alex ; Etani, Takehito ; The Interactive Architecture ; Lab ; Klauer, Julia ; Bruce, Alex ; Ali Tan, Atilla ; Daisuke Yui, Leonard ; Yui, Sahoko ; Fanelsa, Niklas ; place/making ; Rittler, Stefanie ; Bernstein, Jan ; Lung, Carole Frances
boek